Análisis de las necesidades psicoafectivas de personas puérperas en tres hospitales públicos de la provincia de Santa Fe en 2021 (SigMe, 2023)
People going through the puerperium recognize in themselves certain psycho-affective needs that vary according to individual characteristics and experiences, leading to the search for support and affection. These needs are essential for the emotional balance of the person and are important during the puerperium as a transition stage. The aim of this research was to analyze the psycho-affective needs that arose during the puerperium in adults treated in three public hospitals in the cities of Santa Fe, Ceres and Rafaela. A quantitative, observational, analytical, cross-sectional study was carried out with 81 women who agreed to participate voluntarily, through a virtual, anonymous and free survey. 39.5% experienced the puerperal stage as a negative experience. The relationship between the parity and experience variables was significant. In conclusion, it is suggested that health professionals in contact with this population receive training and updates in order to promote the achievement of a positive experience in all puerperal women, through the creation of suitable spaces that meet the needs of each person.
Keywords: psycho-affective needs; support; experience